Measuring the role of stakeholders in management of Yang Highlands Wildlife Reserve Area, Situbondo Districts East Java Indonesia - Muttaqin, Tatag; Raflesia, Fitri; Rahayu, Erni Mukti (Technium Social Sciences Journal, 2022)
Management of forest areas, especially highland wildlife reserves, which requires the collaboration of stakeholders in maintaining sustainability. Collaboration is not easy to do. This is exacerbated by different understandings of the function and status of the area. The different understanding of stakeholders on the function and status of the area in management creates inequality of interests and conflicts. In-depth interviews with purposive sampling were conducted in the April-October 2020 period with 11 stakeholders related to the management activities of the Yang Highlands Wildlife Reserve. The research subjects are internal and external stakeholders who are directly and indirectly involved in the management of the Yang Highlands Wildlife Reserve area with stakeholder analysis. The classification of interests and power of influence of 11 stakeholders in the management of the Yang Highlands Nature Reserve is as follows: a) key players with high interest and power of influence, namely the BBKSDA of East Java, and RKW 23 Argopuro; b) subject, namely Section KSDA Region III Jember and SKW VI Probolinggo; c) context setters, namely the Tourism Office of Situbondo Regency, Bondowoso Police, Head of Baderan Village and Baderan Village Community; d) crowd consisting of Perum Perhutani KPH Bondowoso, BKPH Besuki and KRPH Sumber Malang.